Primer on the metabolic bone diseases and disorders of mineral metabolism (Lippincott-Raven, 1996)
This handbook, in a format designed for quick reference, provides complete information on the symptoms, pathophysiology, diagnosis and treatment of all common and rare bone and mineral disorders. This edition contains an updated and revised table of contents.